COMPONENTS OF INFORMATION AND ANALYTICAL SUPPORT OF THE ENTERPRISE MANAGEMENT SYSTEM IN THE CONDITIONS OF DIGITALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Modern information and analytical support of the enterprise management system should be formed using digital technologies and tools.Purpose of the article: justification of the essence and components of information and analytical support of the enterprise management system in the conditions of digitalization.Methods. Using a system approach, generalization and synthesis methods, the essence of information and analytical support of the enterprise management system was determined; to substantiate its structure, system-structural and compositional approaches, analysis and decomposition methods were used.Results. The essence of information and analytical support of the enterprise management system was clarified. The author's vision of the structure of information and analytical support was substantiated: data collection infrastructure; analytics tools for processing large volumes of data and creating relevant forecasts; integration solutions for interaction between different subsystems and management levels; data protection mechanisms.Conclusions. The development and implementation of intellectual and computer technologies, artificial intelligence as a competitive advantage require the improvement of information and analytical support of the enterprise management system using digital technologies, which will significantly reduce the time spent on the process of making management decisions, increase their validity and efficiency of the enterprise management system.
Keywords: information and analytical support, digitalization, data collection infrastructure, analytics, data processing, integration solutions, data protection mechanisms, digital technologies, management decision-making.